Porter’s Competitive Strategies Influence on Performance of Mobile Telecommunication Companies in Kenya (International Journal of Scientific Research and Management (IJSRM), 2019)
Abstract: The purpose of the study was to establish the relationship between Porter’s competitive strategies and performance of mobile telecommunication companies in Kenya. More specifically the study sought to determine the influence of cost leadership, differentiation and market focus strategies on performance of mobile telecommunication companies in Kenya. The target population of the study comprised of 241 management staff drawn from; Safaricom PLC, Airtel, Telkom and Equitel mobile telecommunication companies in Kenya. A sample of 117 respondents was selected purposively for the study. The study adopted a mixed method of explanatory and cross sectional survey research design approach. The research utilized both primary and secondary data. The data obtained was summarized using descriptive and inferential statistics. Pearson’s correlation was used to determine the relationship between the variables, and multiple regression to determine the influence of Porter’s competitive strategies on performance of mobile telecommunication companies. The study concluded that Porter’s competitive strategies; cost leadership, differentiation and market focus strategies adopted by the telecommunication companies had a positive significant influence on their performance in terms of sales and market share in customer’s subscription. The study recommended that mobile telecommunication companies in Kenya should embrace Porter’s competitive strategies more to continue achieving competitive advantage and enhance their performance.